Development of L-Asparaginase Biobetters: Current Research Status and Review of the Desirable Quality Profiles - Brumano, Larissa Pereira; da Silva, Francisco Vitor Santos; Costa-Silva, Tales Alexandre; Apolinário, Alexsandra Conceição; Santos, João Henrique Picado Madalena; Kleingesinds, Eduardo Krebs; Monteiro, Gisele; Rangel-Yagui, Carlota de Oliveira; Benyahia, Brahim; Junior, Adalberto Pessoa (Frontiers in Bioengineering and Biotechnology, 2019)
L-Asparaginase (ASNase) is a vital component of the first line treatment of acute lymphoblastic leukemia (ALL), an aggressive type of blood cancer expected to afflict over 53,000 people worldwide by 2020, and has recently been shown to have potential for preventing metastasis from solid tumors as well. The ASNase treatment is, however, characterized by a plethora of potential side effects, ranging from immune reactions to severe toxicity. Consequently, in accordance with Quality-by-Design (QbD) principles, ingenious new products tailored to minimize adverse reactions while increasing patient survival have been devised. In the following pages, the reader is invited for a brief discussion on the most recent developments in this field. Firstly, the review presents an outline of the recent improvements on the manufacturing and formulation processes, which can severely influence important aspects of the product quality profile, such as contamination, aggregation and enzymatic activity. Following, the most recent advances in protein engineering applied to the development of biobetter ASNases (i.e. with reduced glutaminase activity, proteolysis resistant and less immunogenic) using techniques such as site-directed mutagenesis, molecular dynamics, PEGylation, PASylation and bioconjugation are discussed. Afterwards, the attention is shifted towards nanomedicine including technologies such as encapsulation and immobilization, which aim at improving ASNase pharmacokinetics. Besides discussing the results of the most innovative and representative academic research, the review provides an overview of the products already available on the market or in the latest stages of development. With this, the review is intended to provide a solid background for the current product development and underpin the discussions on the target quality profile of future ASNase-based pharmaceuticals.